The texture of the gift: Religious touching in the Greco-Roman world - Hughes, Jessica (Body and religion, 2018)
What did ancient religion feel like? This article explores different elements of tactile experience in Greco-Roman sanctuaries, focusing on a group of 'confession stelai' from Roman Asia Minor. Themes explored include the transgressive touching of ancient sacred objects by mortals, and the punitive touching of mortal bodies by the Greco-Roman gods.